1989
DOI: 10.3168/jds.s0022-0302(89)79276-6
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Gland Function During Involution

Abstract: The process of mammary gland involution occurs during the transition from a lactating to a nonlactating state. This transition phase begins after cessation of milk removal and results in changes in mammary secretion composition. Secretion volume declines during involution, as does the concentration of most milk-specific components. Lactoferrin, hydrolytic enzymes, immunoglobulins, and serum-derived components increase in concentration in the secretions during involution. Changes in mammary secretion compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
144
2
24

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(183 citation statements)
references
References 73 publications
13
144
2
24
Order By: Relevance
“…In cows not milked for 48 h, Holst et al [35] observed an accumulation of Golgi vesicles and lipid droplets in mammary epithelial cells. If colchicine (which is known to destructure the cytoskeleton) was injected via the teat canal, similar effects were observed [36]. According to Stelwagen [37], the migration of secretory vesicles could be disturbed by an accumulation of milk in the mammary alveoli because of modifications to the cytoskeleton orchestrated by the opening of tight junctions.…”
Section: Metabolic and Secretion Activitiesmentioning
confidence: 80%
“…In cows not milked for 48 h, Holst et al [35] observed an accumulation of Golgi vesicles and lipid droplets in mammary epithelial cells. If colchicine (which is known to destructure the cytoskeleton) was injected via the teat canal, similar effects were observed [36]. According to Stelwagen [37], the migration of secretory vesicles could be disturbed by an accumulation of milk in the mammary alveoli because of modifications to the cytoskeleton orchestrated by the opening of tight junctions.…”
Section: Metabolic and Secretion Activitiesmentioning
confidence: 80%
“…The MECs in ruminants do not regress to the same extent as occurs in rodent mammary glands, and apparently some synthetic and secretory activity of these cells are maintained throughout the dry period (Holst et al, 1987;Sordillo, 1987;Sordillo and Nickerson, 1988). Sloughing of apoptotic epithelial cells into the alveolar lumen and detachment from the basement membrane observed during the first 2 weeks of involution in rat and mice are not detectable during dry period in dairy cows (Sordillo and Nickerson, 1988;Hurley, 1989;Capuco et al, 1997). Although mammary cell loss does not occur extensively during a standard dry period, tissue remodeling including changes in cell populations, alveolar structure and syntheses of extracellular matrix occur extensively (Holst et al, 1987;Hurley, 1989;Capuco et al, 1997).…”
Section: Altered Dry Periodsmentioning
confidence: 99%
“…Sloughing of apoptotic epithelial cells into the alveolar lumen and detachment from the basement membrane observed during the first 2 weeks of involution in rat and mice are not detectable during dry period in dairy cows (Sordillo and Nickerson, 1988;Hurley, 1989;Capuco et al, 1997). Although mammary cell loss does not occur extensively during a standard dry period, tissue remodeling including changes in cell populations, alveolar structure and syntheses of extracellular matrix occur extensively (Holst et al, 1987;Hurley, 1989;Capuco et al, 1997). Thus, extensive cell turnover occurs during the dry period and the number of epithelial cells rapidly increases during the last 2 months of gestation (Capuco et al, 1997).…”
Section: Altered Dry Periodsmentioning
confidence: 99%
“…İn-volusyonun erken dönemlerinde süte özel olan yağ, laktoz, kazein, α-laktalbumin, β-laktoglobulin miktarları azalırken diğer komponentler olan lökosit, hidrolitik enzimler, immünglobülinler, serum albumin ve laktoferrin ise involusyon boyunca artar ki bu sütteki toplam protein miktarının artışına neden olur. Memede laktoferrin miktarındaki artış involusyonun da aktif olduğunu göstermektedir (7,21). Doğumdan sonraki ilk 48 saat içinde iki önemli koruyucu protein olan laktoferrin ve sIgA miktarı yüksektir.…”
Section: Tartışma Ve Sonuçunclassified